Neuroimaging of classic neuralgic amyotrophy. Issue 6 (23rd September 2016) - Lieba‐Samal, Doris; Jengojan, Suren; Kasprian, Gregor; Wöber, Christian; Bodner, Gerd
ABSTRACT: Introduction : Neuralgic amyotrophy (NA) often imposes diagnostic problems. Recently, MRI and high‐resolution ultrasound (HRUS) have proven useful in diagnosing peripheral nerve disorders. Methods : We performed a chart and imaging review of patients who were examined using neuroimaging and who were referred because of clinically diagnosed NA between March 1, 2014 and May 1, 2015. Results : Six patients were included. All underwent HRUS, and 5 underwent MRI. Time from onset to evaluation ranged from 2 weeks to 6 months. HRUS showed segmental swelling of all clinically affected nerves/trunks. Atrophy of muscles was detected in those assessed >1 month after onset. MRI showed T2‐weighted hyperintensity in all clinically affected nerves, except for the long thoracic nerve, and denervation edema of muscles. Conclusions : HRUS and MRI are valuable diagnostic tools in NA. This could change the diagnostic approach from one now focused on excluding other disorders to confirming NA through imaging markers. Muscle Nerve 54 : 1079–1085, 2016